Agora é Max: a trajetória política de Max de Freitas Mauro (1970-1990) - Lemos, Amarildo Mendes (2014)
The present work deals with the political career of Max de Freitas Mauro in the Espírito Santo and its connection with labour. Accordingly, we began our research with a dissertation origins of this political ideology in Brasil. This political doctrine associated with nationalism, reformism and consolidated at a party that attracted to itself the prestige of workers between 1946 and 1964. During this period, the father of Max Mauro, Saturnino Rangel Mauro, was a prominent politician in the foundation of PTB in the Espírito Santo. Saturnino ascended politically from linking with the political structure implemented in Brazil with the “Revolução de 1930”. From the representation of employees Saturnino attained the rank of state representative for PTB in 1947. The democratic experience of this period, however, was aborted by the 1964 military coup that brought new policy for Brazil, aligning our economy with U.S. by increasing concentration of income and social exclusion. The impacts of economic policies in the Espírito Santo are discussed in this work, since the way it happened capitalist economic modernization that state relates to the structural context experienced by Espírito Santo in the 1980s. Thus, we make a connection between economic modernization in the 1970s and the social exclusion of the next decade, which was the scene of numerous social conflicts also addressed in this work. The political career of Max Mauro overlaps this historical journey experienced by capixaba society. Thus, from research papers, journals, official documents and private collections, present a narrative that seeks to highlight structural and cyclical aspects, ie before that conflicted and contention for hegemony context we point some decisions taken by the governor and his relationship with the established powers. To this end, we analyzed the relationship of Max Mauro the Legislative Assembly, with local authorities and with the centers of power, represented by the companies: Companhia Siderúrgica Tubarão, Aracruz Celulose and Companhia Vale do Rio Doce. Given this situation we assembled to investigate the process of fragmentation of the Brazilian Democratic Movement Party (PMDB), and Max Mauro connection with the party led by the heir Getulism, Leonel de Moura Brizola, and his participation as state governor Espírito Santo, the rise of the Democratic Labor Party (PDT) in this federal state.